If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-1x + 1) + -6x = 30 Reorder the terms: 2(1 + -1x) + -6x = 30 (1 * 2 + -1x * 2) + -6x = 30 (2 + -2x) + -6x = 30 Combine like terms: -2x + -6x = -8x 2 + -8x = 30 Solving 2 + -8x = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -8x = 30 + -2 Combine like terms: 2 + -2 = 0 0 + -8x = 30 + -2 -8x = 30 + -2 Combine like terms: 30 + -2 = 28 -8x = 28 Divide each side by '-8'. x = -3.5 Simplifying x = -3.5
| c-2*c-5-5*c=7 | | 8e^2+64e=-56 | | -2t+4t+-7s=9s | | 3+x=7x-21 | | p+15=15 | | 5(-3x+5)=25 | | 16=10c-c^2 | | 3*w+4*w-2=12 | | 5m+8=78 | | 98-r=28 | | 7(4n-7)(7n-4)=0 | | 0.5*x*(x+4)=20 | | x(2x-5)(5x+2)=0 | | x^2-10+25=4 | | 3+x=7x+-21 | | x^2*8=32 | | 16m+8=32 | | 7(-4-4x)=308 | | 6(6-15)+16+6= | | y^2+12y-45=0 | | (-7)(-5)+(-7)(-4)= | | ln(x)+ln(x+2)=8 | | 11=5*y-4 | | xy=15x^2 | | (2x-8)*(x+3)=0 | | 15=13+2x | | 5-2x=3-14x | | 16e-32=176 | | 9*b+5=23 | | 4(-4p+4)+6p= | | 7(-7x-1)=336 | | 1/2*?(x)=1 |